The Application of The Picture And The Picture Learning Model In Increasing Student Learning Interest in Harapan Pematangsiantar Vocational School: Picture and the picture; Student learning; Learning model - Sitanggang, Anita; Munthe, Melda Veby Ristella (Jurnal Abdimas Multidisiplin, 2023)
The goal of this research is to use a picture and a picture learning model to increase student learning interest in harapan pematangsiantar vocational school. The primary goal of this research was to apply the picture and the picture learning model. picture-and-picture learning model as a learning strategy that employs images as learning media, with the images being paired and logically sequenced. The picture-and-picture learning model is a method of learning that employs images that have been paired or sorted into a logical sequence. This type of learning is active, innovative, creative, and enjoyable. This research investigated and determined the application’s use to pique students’ interest through the use of pictures and the picture learning model. This research employs community service methods in its activities. The researcher uses six steps to examine the data: the first is to send a permit; the second is to form a service implementation team (PKM); the third is to gather teachers in a classroom and teach thematic English materials; the fourth is to divide teachers into several small groups and begin discussion activities; the fifth is to have picture-and-sound learning media distributed to teachers change based on the material and learning topics; and the sixth is to make pictures and pictures that contain vocabulary, pictures, or symbols that are relevant to the topic of discussion as appealing as possible. According to the conclusions of this research, lectures, presentations, modeling, role play, group discussions, discovery learning, and TPR are some of the community service methods used in the activities. With the implementation of these steps, students appear to be very enthusiastic about learning English using the picture-and-picture learning model in conjunction with the use of various learning methods and models, resulting in an improvement in the children’s English skills at SMK HARAPAN Pematang Siantar.